Cytotoxicity Mechanism of a Fungal Inhibitor from a Soil-Derived Streptomyces SP - Jee, Jap Meng (2010)
Effective fungal growth inhibitors are important to drive the development of antifungal compound. In the search for fungal inhibitors, actinomycete H7372 was isolated from a mangrove soil sample from Sabah. Subsequently, in a yeast cell-based screening system, the crude acetone extract prepared from the fermentative culture of H7372 was found to inhibit the growth of the yeasts. The purposes of this study were to establish the phylogenetic position of H7372 and to isolate, characterize and examine the toxicity mechanism of the active fungal growth inhibitor produced by H7372. The partial sequence of 16S rRNA gene was amplified from H7372 for phylogenetic analysis. An active compound was isolated from crude acetone extract of mannitol-soybean fermentation culture and its structure was elucidated. Antifungal properties of the isolated active compound against Candida spp and Aspergillus spp were characterised by minimum inhibitory concentration and time-kill kinetic studies. The consequences of C. glabrata treatment with the active compound were examined by electron microscopy and cDNA microarray. Phylogenetic analysis placed H7372 to its closest relative, S. kasugaensis M338-M1.The isolated active compound, designated as J5, was determined to be the natural (11S, 13S, 9S, 8R)-cycloheximide. All Candida species tested (except C. albicans) and only A. niger were sensitive to J5, with MIC at 24H ranging from 0.313 to 40 μg/ml. The degree of susceptibility shown by some species of Candida, from the most to the least susceptible, were C. krusei, C. glabrata, C. rugosa and C. parapsilosis. J5 is a fungistatic compound which showed total fungicidal effect at 12 times of its MIC when applied to C. glabrata. Treatment with J5 demonstrated profound intracellular and cell surface modifications, such as by marked cell wall thickening, confused cytoplasm, mitochondria loss, and irregular plasma membrane invaginations with detachment of the protoplast from the cell wall. cDNA microarray revealed a total of 60 genes affected by J5 treatment, corresponding to genes involved in protein synthesis, plasma membrane and H+ pumps, mitochondria maintenance and nutrient metabolism. In conclusion, H7372 is a Streptomyces sp. which is closely related to S. kasugaensis M338-M1. The active compound, J5, is a cis-cycloheximide. Comprehensive susceptibility profiles of Candida and Aspergillus species toward J5 were established for the first time and generated new MIC readings for C. krusei (0.313 μg/ml), C. rugosa (0.625 μg/ml), C. glabrata (2.5 μg/ml), C. parapsilosis (2.5 μg/ml), C. tropicalis (5 μg/ml) and A. niger (40 μg/ml). Ultrastructures of J5-treated C. glabrata revealed new evidence on the toxicity mechanisms of cycloheximide on plasma membranes and mitochondria. The gene expression profiles for J5, the cycloheximide treatment, were revealed for the first time in yeast.